Statistical Analysis of Involvement in Income Generating Activities Before and After Joining Self Help Groups (SHGs) and their sustainability – A study (International Journal of Food and Nutritional Sciences, 2023)
The major intention of the present study is to probe SHGs role towards women sustainability in Bengaluru Urban district of Karnataka. Though women contribute both to household and national economy, their work is felt like an extension of household sphere and remain non-monetized. In India microfinance is strengthening the women through collective self help abilities leading to their empowerment which is an essential factor of sustainability. It is viewed that micro finance is essential to overcome poverty, exploitation and create confidence in urban poor who have their aspirations like rural poor. The people living in slums, outskirts need financial assistance in order to meet education, health and marriage of children. Unfortunately so far planners have concentrated only on rural poor and urban poor has been neglected. Women studies reveal that unless and until women are developed their empowerment programmes leading to sustainability has no meaning. Women empowerment has been noticed as a pre requisite condition to reduce poverty in developing nations (Aysha et al., 2018). Participants enjoy the benefit of higher education, decrease in the vulnerability to economic shock and greater empowerment (Tessi Swope, 2005). Against this background on attempt is made to study before and after effects of joining SHGs as far as IGAs are concerned, benefits of sustainability and factors driving women sustainability.